Detecting viable but non-culturable lactic acid bacteria following spray-drying and during storage - Meriam Bouri; Sibel Simsek Yazici; Fikrettin Sahin (The European Chemistry and Biotechnology Journal, 2024)
Microencapsulation with various materials has been used as an efficient method to improve the viability of probiotic bacteria in multiple food products and the human gastrointestinal tract. Although plate count agar is the most commonly used method for evaluating the viability of encapsulated bacteria, it is still far from providing reliable information about the intermediate state between viable and dead bacteria. This study optimized a tetrazolium salt-based colorimetric method for the detection of viable but non-culturable state within encapsulated Lactobacillus rhamnosus and Lactobacillus plantarum probiotic strains. The viability of encapsulated bacteria was assessed after different spray-drying conditions and also during two months of storage at room temperature. The ability to reduce tetrazolium salts of two lactic acid bacteria was verified and calibrated according to the experimental conditions (strains, incubation time, and microencapsulation material). The loss of bacterial cultivability was species-specific and more problematic throughout the processing than during the storage period. An outlet temperature of 73-75 °C yielded a higher viable but non-culturable state level than at 68-69 °C, especially in maltodextrin and trehalose powders. Whey protein was statistically the best carrier in preserving viable and culturable encapsulated bacteria after spray-drying and during storage, as compared to sugar-based carriers. The tetrazolium-optimized method was more sensitive and accurate for the evaluation of viable bacteria in microcapsules as compared to the conventional plate count methods available. It showed the high variability of CFU counts on Man–Rogosa–Sharpe (MRS) agar. This colorimetric technique could be considered a real-time, simple, cost-effective, and reliable alternative to culture-based methods in evaluating probiotic microencapsulation efficiency.